PENGARUH STRUKTUR MODAL, VOLUME PERDAGANGAN SAHAM DAN KAPITALISASI PASAR TERHADAP RETURN SAHAM - Adrian, Muhammad; Ratnasari, Fina (JURNAL AKUNTANSI BARELANG, 2025)
This study investigates the effect of capital structure, stock trading volume, and market capitalization on stock returns in the banking sub-sector. The research employs a quantitative method using secondary data analyzed through panel data regression over a five-year period from 2019 to 2023, with a sample of 47 banking companies. The analysis involves descriptive statistics, classical assumption testing, panel data regression model testing, and hypothesis testing using EViews 12. The findings reveal that capital structure, stock trading volume, and market capitalization each exert a significant partial effect on stock returns. Furthermore, these variables collectively influence stock returns, as demonstrated by the results of simultaneous testing. The coefficient of determination indicates that 47.81 percent of the variation in stock returns is explained by the variables studied, while the remaining 52.19 percent is attributed to other factors beyond the scope of this research. The study concludes that capital structure, stock trading volume, and market capitalization play an important role in shaping stock returns within the banking sub-sector.